Interaction of the yeast gamma-tubulin complex-binding protein Spc72p with Kar1p is essential for microtubule function during karyogamy - Pereira, Gislene; Knop, Michael; Schiebel, Elmar (The EMBO journal, 1999)
The spindle pole body component Kar1p has a function in nuclear fusion during conjugation, a process known as karyogamy. The molecular role of Kar1p during this process is poorly understood. Here we show that the yeast gamma-tubulin complex-binding protein Spc72p interacts directly with the N-terminal domain of Kar1p, thereby targeting the gamma-tubulin complex to the half bridge, a substructure of the spindle pole body, where it organizes microtubules. This binding of Spc72p to Kar1p has only a minor role during vegetative growth, whereas it becomes essential for karyogamy in mating cells, explaining the important role of Kar1p in this process. We also show that the localization of Spc72p within the spindle pole body changes throughout the cell cycle and even more strongly in response to mating pheromone. Taken together, these observations suggest that the relocalization of Spc72p within the spindle pole body is the 'landmark' event in the pheromone-induced reorganization of the cytoplasmic microtubules.